Exploring aphid-virus-wheat interactions using current wheat varieties, aphid control techniques and vector surveys - Girvin, John Jacob III (Kansas State University, 2015)
The bird cherry oat aphid, Rhopalosiphum padi, and one of the viruses it vectors, barley yellow dwarf virus (BYDV), form a very damaging pest unit on cereals. Understanding how people can better manage crops to prevent damage or recognize environmental or geographic factors that put their crops at risk for BYDV could lead to improved virus aphid management strategies. One of the most successful methods for mitigating pest damage is using pest-resistant varieties of crops. Seven candidate wheat varieties were screened for resistance to R. padi, by testing aphid population densities and aphid host choice. Results of this research identified six varieties of wheat that show resistance to R. padi. One of the major knowledge gaps in BYDV management is forecasting potential damage. Our objective was to create viral presence maps, to start building the foundation of correlations between persistent and changing frequency of viruliferous R. padi. The results of BYDV assays in R. padi in wheat fields across Kansas indicated that the amount of BYDV infection in viruliferous aphids changes rapidly from year to year, and differs considerably between geographic regions and field landscape characteristics in Kansas. Neonicotinoid wheat seed treatment is a management technique that reduces R. padi populations. However, a common question among producers is whether or not seed treatments stop viral transmission. Results of greenhouse seed treatment experiments with plants from neonicotinoid treated and untreated seed infested with viruliferous R. padi indicated no significant difference in viral transmission due to seed treatment. This new information about R. padi wheat varietal resistance, geographic distribution of BYDV in Kansas, and neonicotinoid seed treatment creates a better understanding of aphid-virus-wheat interactions. Results from this thesis directly enhance producer ability to forecast risk from BYDV, select wheat varieties that effectively reduce R. padi as a BYDV vector, and to make better decisions about the use of insecticide to reduce BYDV infection.
Keywords: Aphid; Wheat; R. padi; BYDV; Virus; Seed treatment; Agriculture, General (0473); Entomology (0353); Plant Pathology (0480)